Bồi dưỡng kỹ năng đánh giá lớp học cho giảng viên các trung tâm Giáo dục Quốc phòng-An ninh hiện nay - Nguyễn, Thế Hậu (Tạp chí Giáo dục và Xã hội, 2016)
Classroom asessment it undertood as the process of collecting feedback regularly to find out the quality of taeching and students’ reactions to the faculty’s teaching. Bassing on the classroom assessment’s results, teachers regulate teaching to improve learning outcomes for students. The article aims to give in brief some solutions to fostering classroom assessment skills for the faculty.